2019
DOI: 10.1038/s41598-019-48883-x
|View full text |Cite
|
Sign up to set email alerts
|

RNA modulates aggregation of the recombinant mammalian prion protein by direct interaction

Abstract: Recent studies have proposed that nucleic acids act as potential cofactors for protein aggregation and prionogenesis. By means of sedimentation, transmission electron microscopy, circular dichroism, static and dynamic light scattering, we have studied how RNA can influence the aggregation of the murine recombinant prion protein (rPrP). We find that RNA, independent of its sequence, source and size, modulates rPrP aggregation in a bimodal fashion, affecting both the extent and the rate of rPrP aggregation in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 74 publications
4
30
0
Order By: Relevance
“…Such a stoichiometry suggests that each protein needs to be associated with one oligonucleotide to maintain solubility. These figures are in line with what has been observed for other aggregate-prone proteins such as the prion protein and FUS (Kovachev et al, 2019;Maharana et al, 2018). If seed-driven co-precipitation was a major force, a much lower oligo-to-protein ratio would be expected, as only the few seed proteins needs to be associated with the nucleic acid.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Such a stoichiometry suggests that each protein needs to be associated with one oligonucleotide to maintain solubility. These figures are in line with what has been observed for other aggregate-prone proteins such as the prion protein and FUS (Kovachev et al, 2019;Maharana et al, 2018). If seed-driven co-precipitation was a major force, a much lower oligo-to-protein ratio would be expected, as only the few seed proteins needs to be associated with the nucleic acid.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, Maharana et al, showed that for several prion-like proteins, including FUS, these disparate effects can be explained by the ratio of protein to RNA; where excess of RNA promotes solubility and decreased amount of RNA induces phase-transition (Maharana et al, 2018). Similar results have also been observed for p53 and the prion protein (Kovachev et al, 2017;Kovachev et al, 2019).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…rPrP 90-231 at 10 µM in buffer without nucleic acids (black column), or with addition of increasing concentrations of A1 (shades of blue) or A2 (shades of green) or A1_mut (gray column). 5,62 Full-length PrP (PrP 23-231 ) contains at least three sequence motifs that bind NAs, 8 being able to form an interconnected polymer network with NAs. Quantification of rPrP 90-231 droplets number per 100 µm 2 area (bottom).…”
Section: Discussionmentioning
confidence: 99%
“…5,11 Furthermore, the observed NA effects on PrP aggregation are highly dependent on the PrP:NA binding stoichiometry. 5,62 Full-length PrP (PrP 23-231 ) contains at least three sequence motifs that bind NAs, 8 being able to form an interconnected polymer network with NAs. The PrP construct used here, PrP 90-231 , encompasses the second lysine cluster that can interact with NAs, which, when neutralized, results in formation of PrP Sc -like aggregates.…”
Section: Discussionmentioning
confidence: 99%